Illness perception clusters and relationship quality are associated with diabetes distress in adults with Type 2 diabetes. Issue 9 (21st October 2017) - Berry, Emma; Davies, Mark; Dempster, Martin
Abstract: This report aims to augment what is already known about emotional distress in Type 2 diabetes, by assessing the predictive value of illness perception clusters and relationship quality on four subcategories of Diabetes Distress.162 individuals with Type 2 diabetes responded to a postal questionnaire assessing demographics, depression, diabetes distress, illness perceptions and relationship quality. Long-term blood glucose was retrieved from participants' General Practitioner. Three illness perception clusters emerged from the data, capturing three subgroups of participants sharing similar illness perception schemas. Regression analyses were performed across each diabetes distress subscale, with demographics, illness perception clusters, and relationship variables entered into three blocks. Covariates explained 51.1% of the variance in emotional burden, 41% of the variance in regimen-related distress, 20% of the variance in interpersonal distress, and 8.6% of the variance in physician-related distress. Cluster membership was strongly associated with emotional burden, regimen-related distress, and to a lesser degree interpersonal distress, but was not associated with physician-related distress. Relationship quality most strongly predicted regimen-related distress. Illness perception schemas and interpersonal issues influence emotional adjustment in diabetes. This study provides direction for the content of a novel approach to identifying and reducing diabetes distress in people with Type 2 diabetes.